1941
DOI: 10.2307/1968993
|View full text |Cite
|
Sign up to set email alerts
|

Operator-Theoretical Treatment of Markoff's Process and Mean Ergodic Theorem

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
89
0
12

Year Published

1949
1949
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 2 publications
0
89
0
12
Order By: Relevance
“…Thus various authors-notably F. Riesz [28] and Yosida and Kakutani [33]-extended the mean ergodic theorem to an abstract theorem asserting the convergence to a fix point of the means Tnx = (n + l)~122oT'x, where T is a linear transformation of a Banach space E into itself. Alaoglu and Birkhoff [l] then replaced the iterates (T'~) by a semi-group G of linear transformations and showed that convergence of certain general means of transforms of an element x of E is equivalent to the existence and uniqueness of a fix point y in the closed convex hull of the orbit of x under G. The persistence of the customary countability and uniform boundedness restrictions on G in their work, however, severely limits the generality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus various authors-notably F. Riesz [28] and Yosida and Kakutani [33]-extended the mean ergodic theorem to an abstract theorem asserting the convergence to a fix point of the means Tnx = (n + l)~122oT'x, where T is a linear transformation of a Banach space E into itself. Alaoglu and Birkhoff [l] then replaced the iterates (T'~) by a semi-group G of linear transformations and showed that convergence of certain general means of transforms of an element x of E is equivalent to the existence and uniqueness of a fix point y in the closed convex hull of the orbit of x under G. The persistence of the customary countability and uniform boundedness restrictions on G in their work, however, severely limits the generality.…”
mentioning
confidence: 99%
“…This remark covers Hubert space and, more generally, the spaces 2> and /* (p> 1). In the spaces L and / Riesz [28], Birkhoff [l], Kakutani [33] and others observed that a lattice-theoretically bounded set of functions-that is, [x|a(0 Sx(t) =b(t) identically, a, b(E.L or /]-is conditionally weakly compact. In a Lebesgue space L(S) a general criterion for weak compactness (Riesz [28], Dunford and Pettis [12]) yields the conditional weak compactness of Tnx if T is of the classical form Tx(t) = x(<pt), where 0 is a one-to-one measure-preserving transformation of 5 into itself (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What is nowadays called the uniform ergodic theorem goes back to 1941 when Yosida and Kakutani published the study [52]. In this study they obtained conditions 1 on a bounded linear operator T in a Banach space B which are sufficient to provide that the averages n 01 P n01 j=0 T j converge in the uniform operator topology to an operator P in B :…”
Section: Introductionmentioning
confidence: 99%
“…They wrote (see [52] In the rest of the Yosida-Kakutani study the result has been well applied to some problems in the theory of Markov processes. A number of studies have followed.…”
Section: Introductionmentioning
confidence: 99%